Pengembangan Pembelajaran Menulis Cerpen Berbasis Liveworksheet Siswa Kelas VIII SMP - Ema, Ema; Nurhusna, Nurhusna (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This research is a development research (Research & Development) which aims to: 1) produce student worksheets on short story writing learning based on liveworksheets for grade VIII junior high school students; and 2) test the validity of student worksheets on short story writing learning based on liveworksheets for grade VIII junior high school students. The development model used in this study is ADDIE. This research was conducted at SMP IT Yuhana Four Dalle, Gowa Regency. The research instrument used was a validation sheet on the student worksheet. Validity level data were collected using a questionnaire. The subjects of this study were material experts, media experts, and Indonesian language teachers. The object of this study was LKPD using liveworksheets on short story writing material. Data collection techniques used interview and questionnaire techniques. The results of this study indicate the level of validity of LKPD based on liveworksheet on Indonesian language material (writing short stories) for grade VIII junior high school students obtained a score of 3.3 with the category (valid) by material experts, then obtained a score of 3.6 with the category (very valid) by media experts, and obtained a score of 3.6 with the category (very valid) by subject teachers. Based on the validation results carried out by material expert validators, media expert validators, and subject teachers, it can be concluded that student worksheets on short story writing learning based on liveworksheets are declared very valid for use.